2010
DOI: 10.1177/1073858409354385
|View full text |Cite
|
Sign up to set email alerts
|

Is Epilepsy a Preventable Disorder? New Evidence from Animal Models

Abstract: Epilepsy accounts for 0.5% of the global burden of disease, and primary prevention of epilepsy represents one of the three 2007 NINDS Epilepsy Research Benchmarks. In the past decade, efforts to understand and intervene in the process of epileptogenesis have yielded fruitful preventative strategies in animal models. This article reviews the current understanding of epileptogenesis, introduces the concept of a "critical period" for epileptogenesis, and examines strategies for epilepsy prevention in animal model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 181 publications
1
23
0
1
Order By: Relevance
“…Theoretically, this process might be similar to what happens during experimental electrical kindling stimulation of limbic regions where an initial subthreshold stimulus triggers over time, a larger neuronal response resulting in generalized seizures with increasing duration and intensity (Morimoto et al, 2004). Several mechanisms have been identified that may underlie this process, and it is clear that kindling causes functional plasticity in the stimulated focus while also recruiting other networks outside the stimulated area (Giblin and Blumenfeld, 2010;Morimoto et al, 2004). Accordingly, it is necessary to understand when this endogenous stimulation actually begins in WAG/Rij rats, since this will help to guide the search for the best moment for starting a treatment aimed at antiepileptogenesis.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Theoretically, this process might be similar to what happens during experimental electrical kindling stimulation of limbic regions where an initial subthreshold stimulus triggers over time, a larger neuronal response resulting in generalized seizures with increasing duration and intensity (Morimoto et al, 2004). Several mechanisms have been identified that may underlie this process, and it is clear that kindling causes functional plasticity in the stimulated focus while also recruiting other networks outside the stimulated area (Giblin and Blumenfeld, 2010;Morimoto et al, 2004). Accordingly, it is necessary to understand when this endogenous stimulation actually begins in WAG/Rij rats, since this will help to guide the search for the best moment for starting a treatment aimed at antiepileptogenesis.…”
mentioning
confidence: 82%
“…WAG/Rij rats are currently considered a plausible model of absence epileptogenesis or more generally, a genetic animal model of epileptogenesis (Blumenfeld et al, 2008;Giblin and Blumenfeld, 2010;White and Loscher, 2014). This point is strongly supported by the recent clinical data demonstrating a potential antiepileptogenic effect of EHT in childhood absence epilepsy, similarly to its effects in this strain (Berg et al, 2014;Blumenfeld et al, 2008).…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
“…While there has been little electrophysiological work looking at synaptic plasticity in these projections, there have been a number of electrophysiological studies looking at epileptiform activity in the perirhinal cortex, especially utilising the kindling model of temporal lobe epilepsy (Goddard, 1967;Giblin and Blumenfeld, 2010). Slices of perirhinal cortex from amygdala-kindled rats showed abnormal generation and synchronisation of fEPSPs following tetanus stimulation compared to slices taken from control rats (Matsumoto et al, 1996).…”
Section: Subcortical Afferents and Efferents Of The Perirhinal Cortexmentioning
confidence: 99%
“…Future preclinical and clinical studies that continue to identify and validate neuroimaging biomarkers, improve imaging methods, use multimodal imaging, and combine imaging with other validated techniques (e.g., EEG), will make further strides towards our better understanding of the epileptogenic process. There is also growing evidence from animal models that epilepsy is a preventable disorder (see [118] for a review), with the identification of promising antiepileptogenic treatments, including rapamycin and sodium selenate [118,119]. However, to maximize the translatability of these findings to human patients it is important that future preclinical anti-epileptogenic studies utilize valid and clinically applicable biomarkers, such as neuroimaging, in their assessment of these therapies [e.g., 120].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%